Complex Small-Molecule Architectures Regulate Phenotypic Plasticity in a Nematode - Bose, Neelanjan (2012)
Microorganisms and plants produce a large diversity of secondary metabolites, whereas analyses of metazoan metabolomes have yielded comparatively few types of small molecules. We show that the nematode Pristionchus pacificus constructs elaborate molecular architectures from modified building blocks of primary metabolism, including an unusual xylopyranose-based nucleoside. These compounds act as signaling molecules controlling adult phenotypic plasticity and development and provide striking examples for modular generation of structural diversity in metazoans.